2012
DOI: 10.1096/fj.11-194878
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial pulsed magnetic field stimulation facilitates reorganization of abnormal neural circuits and corrects behavioral deficits without disrupting normal connectivity

Abstract: Although the organization of neuronal circuitry is shaped by activity patterns, the capacity to modify and/or optimize the structure and function of whole projection pathways using external stimuli is poorly defined. We investigate whether neuronal activity induced by pulsed magnetic fields (PMFs) alters brain structure and function. We delivered low-intensity PMFs to the posterior cranium of awake, unrestrained mice (wild-type and ephrin-A2A5(-/-)) that have disorganized retinocollicular circuitry and associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
154
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(171 citation statements)
references
References 120 publications
12
154
5
Order By: Relevance
“…Although ephrin-A2 -/- mice have abnormal brain circuitry and associated abnormal behaviours, in the present study, the previously reported learning deficit 17 was not observed due to low levels of food deprivation 18 . The absence of observed behavioural and structural change is consistent with previously reported rTMS specificity for abnormal systems 8, 19 . Furthermore, the lack of adverse effects in our long term study contributes evidence that rTMS is safe to use in healthy control participants 20 .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Although ephrin-A2 -/- mice have abnormal brain circuitry and associated abnormal behaviours, in the present study, the previously reported learning deficit 17 was not observed due to low levels of food deprivation 18 . The absence of observed behavioural and structural change is consistent with previously reported rTMS specificity for abnormal systems 8, 19 . Furthermore, the lack of adverse effects in our long term study contributes evidence that rTMS is safe to use in healthy control participants 20 .…”
Section: Discussionsupporting
confidence: 92%
“…Although the mice learned the task, their performance remained suboptimal due to lack of motivation to obtain food rewards through insufficient food restriction 18 and neither learning behaviour, nor hippocampal spine density were affected by long term rTMS. Our negative results are consistent with previous data showing that rTMS has a selective effect on abnormal or injured brain circuitry 19 , and the lack of deleterious side effects observed in normal human subjects 8, 20 .…”
Section: Introductionsupporting
confidence: 93%
See 3 more Smart Citations